Evaluating the Impact of a Performance‐Based Methodology on Transfer of Training. Issue 1 (17th April 2013) - Kazbour, Richard R.; McGee, Heather M.; Mooney, Timothy; Masica, Laura; Brinkerhoff, Robert O.
Abstract Transfer of training is the degree to which trainees can apply the knowledge, skills, and attitudes gained in training to the job. Currently only between 5% and 20% of what is learned in training is ever applied on the job. At this time, little is known about the effects of work environment factors, such as support, feedback, and goal setting, on training transfer. We utilized a quasi‐experimental between‐groups design using surveys, interviews, and behavioral measures to evaluate the impact of performance‐based work environment factors on training transfer. Results indicated that participants in the experimental group reported a higher level of training transfer than those in the control group. These findings suggest that a performance‐based approach to training can be an effective method to increase the likelihood that employees transfer training knowledge to the job context.